Gejolak di Awal Gerak: Perwari dalam Kemelut Revolusi Indonesia - Galuh Ambar Sasi (Universitas Gadjah Mada, 2022)
The historical narrative of the Indonesian women’s movement is solely about the congressional activities and their results without giving explanation on the meaning and historical context of the movement. This can be seen from the discourse of Indonesian women’s movement during the revolutionary period, which generally centered on four main points, i.e. women’s mobilization in the Red Cross, women paramilitary troops, public kitchen, as well as organizational change and its congress. As an alternative, in this article I examine the first five months of Perwari (the Women Association of Republic Indonesia), its dynamic and historical context. The research finds out that differences of ideologies, perceptions, and expectations about the Indonesian revolution influenced the direction of women’s movement, triggering internal conflict that eventually destroyed them.